1986
DOI: 10.1002/jgt.3190100209
|View full text |Cite
|
Sign up to set email alerts
|

Saturated graphs with minimal number of edges

Abstract: Let F = {F1,…} be a given class of forbidden graphs. A graph G is called F‐saturated if no Fi ∈ F is a subgraph of G but the addition of an arbitrary new edge gives a forbidden subgraph. In this paper the minimal number of edges in F‐saturated graphs is examined. General estimations are given and the structure of minimal graphs is described for some special forbidden graphs (stars, paths, m pairwise disjoint edges).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
134
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 4 publications
4
134
0
Order By: Relevance
“…Therefore for n > 2r 6 we have δ i = r − 1 for all i. Each of the x i 's has one neighbour in each adjacent part and is in a copy of K r .…”
Section: Extra-saturation Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore for n > 2r 6 we have δ i = r − 1 for all i. Each of the x i 's has one neighbour in each adjacent part and is in a copy of K r .…”
Section: Extra-saturation Numbersmentioning
confidence: 99%
“…The study of saturation numbers was initiated by Erdős, Hajnal and Moon [3] when they proved that sat(K r , n) = (r − 2)(n − 1 2 (r − 1)). It was later shown by Kászonyi and Tuza in [6] that cliques have the largest saturation number of any graph on r vertices which in particular implies that for any H the saturation number sat(H, n) grows linearly in n.…”
Section: Introductionmentioning
confidence: 97%
“…The saturation number for complete graphs was determined in [2]. A systematic study by Kászonyi and Tuza [8] found the best known general upper bound for sat(n, H) in terms of the independence number of H. The saturation number is now known, often precisely, for many graphs; for these results and related problems in graph theory we refer the reader to the thorough survey of J. Faudree, R. Faudree, and Schmitt [3].…”
Section: Introductionmentioning
confidence: 99%
“…This can viewed as the dual function of the celebrated Turán function ex(n, F ), the maximum number of edges in an F -saturated graph of order n. One crucial difference is that, for any fixed F , sat(n, F ) is bounded by a linear function of n (as it was shown by Kászonyi and Tuza [20]) while ex(n, F ) may be quadratic in n.…”
mentioning
confidence: 99%
“…The case of a star K 1,s is easy, see [20]. Pikhurko [25] computed the saturation function of K t * K s = K 1,...,1,s exactly when n ≥ n 0 (s, t).…”
mentioning
confidence: 99%